The Covid-19 pandemic effects in rural areas: Turning challenges into opportunities for rural regeneration - de Luca, Claudia; Tondelli, Simona; Åberg, Hanna Elisabeth (TeMA - Journal of Land Use, Mobility and Environment, 2020)
Rural communities tell us the story of a thousand of years of collaboration between nature, culture and humans. The current Covid-19 pandemic is considerably threating rural areas, posing challenges exacerbated by low available financial resources, not easily accessible health services and greater isolation. Rural areas are also considered safe shelters characterized by better daily living conditions thanks to easy to maintain social distancing and access to nature, to cultural and nature-based recreation activities. The Covid-19 crisis is revealing the crucial role of natural and cultural heritage for social cohesion, local development and mental wellbeing. The paper presents some responses to the Covid-19 crisis collected through an open call for action within the RURITAGE project. It aims at show how rural areas can cope with emergencies and it builds the basis to rethink the current crisis as a crucial tipping point for a resilient development of rural territories. It is key to overcome the idea of rural areas as mere food production system, calling for a broader vision of rural communities as poles of development based on local heritage, natural resources, creativity and social inclusion as essential elements to regenerate rural areas and to rapidly support their transition towards sustainable future.